Lubrication properties of model dairy beverages: Effect of the characteristics of protein dispersions and emulsions. (July 2022) - Ji, Lei; Cornacchia, Leonardo; Sala, Guido; Scholten, Elke
Graphical abstract: Highlights: Size, morphology, and hydrophobicity of components are critical factors for lubrication properties. Unstable emulsions under shear are more efficient than stable emulsion at reducing friction. Protein molecules dominated lubrication more than protein aggregates and emulsion droplets in mixed systems. Lubricants behave differently in single- and multi-component systems. Abstract: In this study we investigated the individual contribution of different ingredients to the lubrication properties of dairy-based model beverages containing whey protein (native or aggregated), micellar casein and emulsified oil in different combinations. In single-component systems, whey protein isolate (WPI) solutions showed the lowest friction coefficients of all protein samples. Whey protein aggregates (WPA, ∼247 nm, irregular morphology) led to higher friction coefficients than micellar casein isolate (MCI) with comparable size (∼207 nm, near spherical shape). When protein particles were combined, i.e. WPA and MCI, lubrication was not much affected. However, when WPI was added to either WPA or MCI, higher friction coefficients were observed compared to single-component systems. Emulsions (droplet size ∼ 440 nm) provided better lubrication than the protein samples. Oil droplets stabilized by soy lecithin (SL) were more efficient at reducing friction than those stabilized by WPI. The friction coefficient of SE strongly increased in the presence of WPI. In comparison, lubrication of WE was less affected by the addition of WPI. These results show that different proteins affect the lubrication properties of emulsions stabilized with different emulsifiers in a different way. Our research also indicates that multicomponent systems are complex, and that control over the lubrication properties requires a better understanding of the contribution of individual components.